2017
DOI: 10.1128/jvi.01668-16
|View full text |Cite
|
Sign up to set email alerts
|

An Optimized Hepatitis C Virus E2 Glycoprotein Core Adopts a Functional Homodimer That Efficiently Blocks Virus Entry

Abstract: The hepatitis C virus (HCV) envelope glycoprotein E2 is the major target of broadly neutralizing antibodies in vivo and is the focus of efforts in the rational design of a universal B cell vaccine against HCV. The E2 glycoprotein exhibits a high degree of amino acid variability which localizes to three discrete regions: hypervariable region 1 (HVR1), hypervariable region 2 (HVR2), and the intergenotypic variable region (igVR). All three variable regions contribute to immune evasion and/or isolate-specific stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 62 publications
1
13
0
1
Order By: Relevance
“…Recombinant E2 (rE2) protein was derived from HCV H77 genotype 1a (GenBank accession number AF011751) and HCV UNK3a.13.6 genotype 3a (GenBank accession number AY894683). E2 regions corresponding to HCV H77 genotype 1a isolate poly-protein amino acid residues 384 to 661, introduced into pcDNA3.1 expression vector (Life Technologies, Carlsbad, CA, USA) with a C-terminal Avitag and six-histidine epitope tag (6-His) [57,58] and codon-optimised, were purchased from GeneArt (Thermo Fisher Scientific, Waltham, MA, USA).…”
Section: Construction and Expression Of Recombinant E2mentioning
confidence: 99%
“…Recombinant E2 (rE2) protein was derived from HCV H77 genotype 1a (GenBank accession number AF011751) and HCV UNK3a.13.6 genotype 3a (GenBank accession number AY894683). E2 regions corresponding to HCV H77 genotype 1a isolate poly-protein amino acid residues 384 to 661, introduced into pcDNA3.1 expression vector (Life Technologies, Carlsbad, CA, USA) with a C-terminal Avitag and six-histidine epitope tag (6-His) [57,58] and codon-optimised, were purchased from GeneArt (Thermo Fisher Scientific, Waltham, MA, USA).…”
Section: Construction and Expression Of Recombinant E2mentioning
confidence: 99%
“…It was recently found that HVR1-mediated NAb protection could be increased even further through the binding of HVR1-specific antibodies, possibly by increased steric occlusion mediated by HVR1-bound antibody ( 137 ). The HVR1-mediated NAb protection may function in concert with other highly variable region in E2 ( 140 , 141 ), but how this interplay functions is largely unknown.…”
Section: Hvr1 Protects Hcv From Neutralizing Antibodiesmentioning
confidence: 99%
“…The majority of bNAbs target the E2 subunit, while only a few bNAbs against E1 have been isolated [ 29 , 30 , 31 , 32 ]. Soluble recombinant versions of the ectodomain of E2 maintain receptor-binding properties and are recognized by most anti-E2 bNAbs, suggesting that recombinant E2 (partly) retains its conformation [ 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%